(untitled) (Research, Society and Development, 2021)
Introduction: as NCDs portray a major and important public health problem in all countries, among these diseases are cardiovascular diseases (CVD), responsible for a large mortality rate worldwide. Objective: Thus, the present study aims to describe findings in the literature that establish the relationship between vitamin D deficiency, with the imbalance of the microbiota and the development of cardiovascular diseases. Methodology: The methodology used was a literature review of narrative character. Data collection was carried out on sites such as Scielo (Scientific Electronic Library Online), PubMed (Database of Medical Publications) and Google Scholar in Portuguese and English. Articles, theses, monographs and websites were included that presented contents and titles that fit the studied theme and in the period from 2011 to 2021, in Portuguese or other languages ​​such as English, and those that did not meet these criteria were excluded. . Results and speeches: There are indications of the participation of vitamin D in homeostasis of the cardiovascular system through the mediation of microbiota regulation and the inflammatory state. Conclusion: Even with current studies, more studies and research are needed to evaluate such a relationship in order to clarify the processes involving vitamin D, microbiota and cardiovascular system and their respective roles in increased cardiovascular risk, so that it is possible to establish not only future one’s lines of treatment, but also means of prevention.